2014
DOI: 10.1371/journal.pone.0087281
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Cell Proliferation Controlled by ERK Activity-Dependent Surface Expression of PDGFRA

Abstract: Increased PDGFRA signaling is an essential pathogenic factor in many subtypes of gliomas. In this context the cell surface expression of PDGFRA is an important determinant of ligand sensing in the glioma microenvironment. However, the regulation of spatial distribution of PDGFRA in glioma cells remains poorly characterized. Here, we report that cell surface PDGFRA expression in gliomas is negatively regulated by an ERK-dependent mechanism, resulting in reduced proliferation of glioma cells. Glioma tumor tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Initially, a decline was noted in phosphorylated levels of ERK; however, phospho-ERK levels were notably enhanced between 3 and 18 h of U0126 treatment in the glioma cell lines. 12,13 Downstream of kinase 1 (DOK1) is overexpressed in different glioma cancer cell lines and has been shown to undergo tyrosine phosphorylation in PDGF-BB-treated glioma cells. Detailed mechanistic insights revealed that phosphorylation of p130Cas at tyrosine residues and activation of Rap1 were impaired in DOK1-silenced or DOK1 mutant expressing glioma cells.…”
Section: Defects In Pdgf Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Initially, a decline was noted in phosphorylated levels of ERK; however, phospho-ERK levels were notably enhanced between 3 and 18 h of U0126 treatment in the glioma cell lines. 12,13 Downstream of kinase 1 (DOK1) is overexpressed in different glioma cancer cell lines and has been shown to undergo tyrosine phosphorylation in PDGF-BB-treated glioma cells. Detailed mechanistic insights revealed that phosphorylation of p130Cas at tyrosine residues and activation of Rap1 were impaired in DOK1-silenced or DOK1 mutant expressing glioma cells.…”
Section: Defects In Pdgf Pathwaymentioning
confidence: 99%
“…36 There is an exciting piece of evidence suggesting that miR-34a negatively regulates PDGFRβ in cultured rat mesangial cells. 12,13 Likewise, NSCLC cells have downregulated miR-34a/c and upregulated PDGFRα/β that impaired TRAIL-mediated apoptosis. It was further suggested that gene silencing of PDGFRα/β or overexpression of miR-34a/c in NSCLC cells restored TRAIL-induced apoptosis.…”
Section: Defects In Pdgf Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…In the central nervous system (CNS), Erk1/2 are essential for different forms of synaptic long‐term plasticity, which is referred to as the molecular mechanism proposed to underlie learning and memory. Aberrant Erk1/2 activity is also thought to contribute importantly to CNS disorders, such as epilepsy, Alzheimer's disease, stroke, and cancer . In all these disorders, the availability of selective and potent Erk1/2 inhibitors will be indispensable for the functional investigation of the individual role of Erk1/2 in neuronal signaling in both, the normal and diseased CNS.…”
Section: Figurementioning
confidence: 99%